Roadblocks and Opportunities to the Implementation of Novel Therapies for Acute Kidney Injury: A Narrative Review. Issue 1 (October 2019) - Misra, Paraish S.; Silva e Silva, Vanessa; Collister, David
Background: Acute kidney injury (AKI) is a complex and heterogeneous clinical syndrome with limited effective treatment options. Therefore, a coherent research structure considering AKI pathophysiology, treatment, translation, and implementation is critical to advancing patient care in this area. Purpose of review: In this narrative review, we discuss novel therapies for AKI from their journey from bench to bedside to population and focus on roadblocks and opportunities to their successful implementation. Sources of information: Peer-reviewed articles, opinion pieces from research leaders and research funding agencies, and clinical and research expertise. Methods: This narrative review details the challenges of translation of preclinical studies in AKI and highlights trending research areas and innovative designs in the field. Key developments in preclinical research, clinical trials, and knowledge translation are discussed. Furthermore, this article discusses the current need to involve patients in clinical research and the barriers and opportunities for effective knowledge translation. Key findings: Preclinical studies have largely been unsuccessful in generating novel therapies for AKI, due both to the complexity and heterogeneity of the disease, as well as the limitations of commonly available preclinical models of AKI. The emergence of kidney organoid technology may be an opportunity to reverse this trend. However, the roadblocks encountered at the bench have not precluded researchers from running well-designed and impactful clinical trials, and the field of renal replacement therapy in AKI is highlighted as an area that has been particularly active. Meanwhile, knowledge translation initiatives are bolstered by the presence of large administrative databases to permit ongoing monitoring of clinical practices and outcomes, with research output from such evaluations having the potential to directly impact patient care and inform the generation of meaningful clinical practice guidelines. Limitations: There are limited objective data examining the process of knowledge creation and translation in AKI, and as such the opinions and research areas of the authors are significantly drawn upon in the discussion. Implications: The use of an organized knowledge-to-action framework involving multiple stakeholders, especially patient partners, is critical to translating basic research findings to improvements in patient care in AKI, an area where effective treatment options are lacking.